Case Report of Fibrodysplasia Ossificans Progressiva (Indian Journal of Case Reports, 2016)
Fibrodysplasia ossificans progressiva is a rare genetic disease characterized by widespread soft tissue ossification and congenital stigmata of the extremities. We report a male patient who had bilateral hallux valgus since birth. Other noticed anomalies included multiple swellings over the back, stiffness of lower back area, multiple joints, restricting movement of spine, shoulders, elbows, and right hip and right knee. Patient was not able to bend forward, squat or turn head to either side. Patient also had multiple foci of ossification developed over left knee, and back region. All swellings and restrictions were painless.